N2 Gas-Flushing Prevents Bacteria-Promoted Lipolysis and Proteolysis and Alleviates Auto-Oxidation in Bovine Raw Milk During Cold-Storage - Munsch-Alatossava, Patricia; Ibarra, Dominique; Youbi-Idrissi, Mohammed; Alatossava, Tapani (Frontiers in Sustainable Food Systems, 2019)
Worldwide, tremendous amounts of food, including milk and dairy products, are lost or wasted. Although refrigeration permits longer storage of raw milk, low temperatures still do not prevent the action of other abiotic and biotic factors that promote biochemical, chemical, microbial, sensorial and nutritional changes in raw milk, which also affect milk-derived dairy products. Treatment by N2 gas flushing showed great potential in preserving the microbiological quality of raw milk during storage at low and milder temperatures. Here, we examined the impact of cold storage (at 6°C up to 7 days), on the ascorbic acid content, extent of auto-oxidation, and on levels of lipolysis and proteolysis along with bacterial growth, in three raw milk samples in the presence or absence of N2. When N2 gas was applied, lower levels of lipolysis and proteolysis were found to coincide with the detection of lower numbers of bacterial lipase and protease producers in raw milk. Furthermore, lower auto-oxidation was detected in N2-treated samples than in only cold stored controls. By demonstrating that key components of milk were better preserved during cold storage, the present study further highlights the advantages of the N2 flushing treatment in terms of preserving the quality and safety of raw milk and its derived dairy products.